2018
DOI: 10.1002/ange.201806551
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine‐Assembled Nanodots as Photosensitizers for Highly Efficient Type I Photoreactions in Photodynamic Therapy

Abstract: Owing to their unique,n anoscale related optical properties,n anostructures assembled from molecular photosensitizers (PSs) have interesting applications in phototheranostics.H owever,m ost nanostructured PS assemblies are super-quenched, thus,p reventing their use in photodynamic therapy( PDT). Although some of these materials undergo stimuli-responsive disassembly,which leads to partial recovery of PDT activity,t heir therapeutic potentials are unsatisfactory owingt oalimited ability to promote generation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 42 publications
0
48
0
Order By: Relevance
“…However, this quite excessive temperature can disrupt nature tissues and lead to other diseases or problems [ 7 , 8 ]. A mass of works have confirmed that reactive oxygen species (ROS) such as 1 O 2 can kill bacteria by destroying its protein or DNA [ [9] , [10] , [11] ]. By combining photosensitizer, a relevant light can stimulate material to produce ROS and kill bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…However, this quite excessive temperature can disrupt nature tissues and lead to other diseases or problems [ 7 , 8 ]. A mass of works have confirmed that reactive oxygen species (ROS) such as 1 O 2 can kill bacteria by destroying its protein or DNA [ [9] , [10] , [11] ]. By combining photosensitizer, a relevant light can stimulate material to produce ROS and kill bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Since targeting mitochondria has emerged as a new strategy for improved therapeutic efficiency, the AIE‐based strategy might provide a new platform for image‐guided phototherapy with the assistance of mitochondrial‐targeted imaging . That is, the enrichment of AIEgen probes in cancer cell mitochondria is expected to effectively kill tumor cells with significantly light‐induced intracellular reactive oxygen species (ROS) generation.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the limitation of TsCuPc, red light (l > 630 nm) was used in this work. As metallophthalocyanines have been widely used for in vivo applications such as photodynamic therapy, [16] we envision that further investigation by using as imilar principle would make the CNNS-metallophthalocyanine system suitable for NIR. In addition, owing to the lack of suitable photoactive materials,v ery few works regarding PEC biosensing with red light have been reported, such as using TiO 2 /CdTe/NaYF 4 :Yb/Er,Z nO nanorods/naphthalocyanine, TiO 2 nanotube photonic crystals, Ag NPs/Ag 2 SQ Ds, and Ag 2 S/ NaYF 4 :Yb/Er.…”
Section: Resultsmentioning
confidence: 99%
“…In photosynthesis by plants, which converts solar energy to biomass and providese nergy for humans, porphyrin systems play an irreplaceabler ole. [15] Among them, metallophthalocyanines (MPcs), whichc ontain alternating C=Ca nd C=Nb onds, lead to excellent harvesting of red and near-infrared light of the solar spectrum for wide applications,f or example, organic solar cells, photodynamic cancer therapy, [16] heat absorbers, gas sensors, [17] and bioimaging. [18] Given the unique characteristic of MPcs, coupling of molecular MPc antennas on semicon-ductingC Nb yp-p stacking interaction is ar easonable solution to address the above difficulties; however,s ensitized CN responsive to long-wavelengthl ight for PEC biosensing has not been explored, and only very limited work regarding successful PECb iosensingu nder long-wavelength light has been reported so far.…”
Section: Introductionmentioning
confidence: 99%